An interpretative phenomenological analysis of the player development manager role in Australian professional sports - Stansen, C.; Chambers, T. P. (Qualitative Research in Sport, Exercise and Health, 2019)
Emerging evidence within the context of athlete mental health and well-being has pointed towards the benefits of creating holistic support programmes that assist athletes with a myriad of issues. In this study, the role of player development managers (PDM) within Australian professional sports, and the club environment in which they work was examined. Guided by an interpretative phenomenological analysis approach, this qualitative study explored the lived experiences of 13 PDMs from the Australian Football League, cricket and rugby union. Analyses revealed four higher order themes related to the player development role including PDM role, individual qualities, support services and club environment. As the first study of its nature, the findings provide a platform for future investigations of player development to enrich our understanding of how the role assists professional athletes to navigate the challenges associated with a sporting career.